Soil Moisture Content as a Determining Factor for Machinery Selection - D. Elfadil, Abdelkarim; A. Ali, Mohammed; I..Mohammed, Hassan (Gezira Journal of Agricultural Science; Vol 2 No 2 (2004), 2021)
By applying the soil moisture content (SMC) prediction model to the weather data for the period from 1981-1993, the suitable workdays were obtained. Testing these results from the Rahad Scheme data records showed high significance. The correlation coefficient was found to be 0.99. show the effect of timeliness cost, a utilization factor (Ut) was determined by dividing the available working days by the total days. The utilization factor is then adjusted using a range of reliability from 30-80% depending on spare part availability and skilled labour. Further analysis were made to demonstrate the effect of workable days on the selection of implement width and cost using good, bad and average rainy seasons and different levels of reliabilities. It was found that the machine width was by the rainfall frequency.